Eight Weeks of Aerobic Exercise and Prescribed Diet (Low in Carbohydrate and High Protein) Improve Mental Health in Obese Women - Yagmaee, Fateme (International Journal of Sport Studies for Health, 2021)
Objectives: Although, the association between mental health and obesity has been reported in different studies, the relationship between dietary carbohydrate intake and mental health is not well understood. The aim of this study was to investigate the association of a diet (low in carbohydrate and high protein) along with aerobic exercise on mental health in obese individuals. Methods: In this quasi-experimental study, 30 obese women (20 - 35 years; 80 - 100 kg, 160 ± 5.1 cm and body mass index (above 30) who lived in Qazvin, Iran were selected voluntarily. Dietary intakes during the past one- month was assessed using a quantitative questionnaire on food frequency. Additionally, Beck Anxiety Inventory was used to monitor the rate of depression. Subjects were then randomly divided into experimental and control groups. The experimental group received a balanced diet that was low in carbohydrates and high in protein based on the calculation of their metabolism, while at the same time engaging in aerobic exercise (walking) for 8 weeks with 75% of the maximum heart rate. Control group did not receive any intervention during the study period. The aerobic program was performed for eight weeks (4 sessions per week and 50 minutes per session). Results: The results showed that the rate of depression was significantly improved in experimental group (P = 0.001), however, no significant change was found for control group (P = 0.17) Conclusions: The present study showed that a low carb and high protein diet is positively associated with mental health improvement (anxiety, stress and depression).